PREFACE: Reformation of Health System in Indonesia - Erfen Gustiawan Suwangto (Faculty of Medicine, Public Health, and Nursing, 2022)
We’re looking forward to reformation era of health sector in Indonesia since the declaration of Perkumpulan Dokter Seluruh Indonesia (Indonesian Doctors Association). The reformation process is starting with ongoing the revision of Medical Practice Act and Medical Education Act.